Students’ Learning Strategy in Vocabulary of The Eleventh Grade of Ma Al-Hikmah Sunan Kudus Bunga Mayang Academic Year 2025/2026 - Aria Aditia; Rulik Setiani (Universitas Cokroaminoto Palopo, 2026)
This research was conducted based on the concern that many EFL students still experience difficulties in mastering vocabulary, even though vocabulary plays a central role in developing listening, speaking, reading, and writing skills. In many classrooms, vocabulary learning is often limited to memorizing word lists without helping students understand how to plan, access resources, and process new words effectively. Therefore, this research aimed to describe in depth the vocabulary learning strategies used by eleventh-grade students of MA Al-Hikmah Sunan Kudus Bunga Mayang in the academic year 2025/2026, particularly how they organize their learning through planning, resource selection, and vocabulary processing. This research applied a descriptive qualitative design. The participants were eight high-achieving students selected based on their English scores. Data were collected through an open-ended questionnaire designed according to Nation’s taxonomy of vocabulary learning strategies, covering planning, resources, and processes. The instrument was validated by an expert before distribution. Data analysis followed the Miles and Huberman framework, including data collection, reduction, display, and verification, to ensure that the findings were grounded in participants’ actual responses. The results showed that students consistently applied three interconnected strategy categories. In the planning stage, they set daily or weekly vocabulary targets and chose specific study times to maintain learning consistency. In terms of resources, students combined digital media such as films, music, social media, and online games with formal materials like textbooks and dictionaries. In the processing stage, they actively engaged in note-taking, repetition, flashcards, mind mapping, and productive use of vocabulary in writing and conversation. These findings indicate that effective vocabulary learning emerges from a balance between structured planning, varied resource utilization, and active cognitive engagement.